Bank capital and the European recovery from the COVID-19 crisis - Moritz Schularick; Sascha Steffen; Tobias H. Tröger (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
Do current levels of bank capital in Europe suffice to support a swift recovery from the COVID-19 crisis? Recent research shows that a well-capitalized banking sector is a major factor driving the speed and breadth of recoveries from economic downturns. In particular, loan supply is negatively affected by low levels of capital. We estimate a capital shortfall in European banks of up to 600 billion euro in a severe scenario, and around 143 billion euro in a moderate scenario. We propose a precautionary recapitalization on the European level that puts the European Stability Mechanism (ESM) center stage. This proposal would cut through the sovereign-bank nexus, safeguard financial stability, and position the Eurozone for a quick recovery from the pandemic.
Keywords: 330